The Background and Core Doctrines of the Khawarij and Murji'ah - Fitra Wahyuni; Indo Santalia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the background of the emergence as well as the principals of thought of two early theological schools in Islam, namely Khawarij and Murji’ah. Both schools were born from political upheavals after the death of the Prophet, especially during the conflict between Ali ibn Abi Talib and Muawiyah ibn Abi Sufyan. The Khawarij flourished as a radical group that disbelieved perpetrators of grave sins and rejected rulers’ perceived unjust authority. Instead, Murji’ah presents as a reaction to a situation fraught with accusations of infidelity by postponing the assessment of one’s faith and leaving it to Allah. This research uses a literature study-based descriptive qualitative approach, with thematic and comparative analysis to understand the differences in faith concepts, political attitudes, as well as the theological impact of both schools. The results of the study show that Khawarij and Murji’ah occupy two extreme poles in understanding the relationship between faith and charity: Khawarij are hardline and revolutionary in nature, while Murji’ah tends to be moderate and tolerant. This study affirms the importance of moderation as a middle path in avoiding extremism and overly permissive attitudes in religion.